Macroscopic bioinspired graphene sponge modified with in-situ grown carbon nanowires and its electromagnetic properties. (January 2017) - Kong, Luo; Yin, Xiaowei; Han, Meikang; Yuan, Xiaoyan; Hou, Zexin; Ye, Fang; Zhang, Litong; Cheng, Laifei; Xu, Zhanwei; Huang, Jianfeng
Abstract: Three-dimensional (3D) macroscopic covalently bonded carbon nanowires/graphene (CNWs/G) architectures can achieve the extraordinary properties based on theoretical work. A series of 3D structures have been recently fabricated. However, these architectures are far from theoretical model because CNWs are difficult to perfectly connect with the graphene substrate which has extremely low surface energy and complex internal structure. Here, we highlight a bioinspired approach based on polydopamine interface buffer for the fabrication of 3D macroscopic CNWs/G sponge composite. CNWs uniformly grow on graphene substrate through covalent CC bonding. The defects of CNWs and junction interface between CNWs with graphene greatly influence the electronic transport, leading to the strong polarization and electromagnetic wave attenuation under alternating electromagnetic field. Owing to this unique 3D architecture, the CNWs/G composite attains ultralight density and outstanding electromagnetic attenuation capability. CNWs/G/poly(dimethyl siloxane) composite exhibits the electromagnetic interference shielding effectiveness of 36 dB in X-band (8.2–12.4 GHz) and the composite density is 97.1 mg/cm 3 . The macroscopic 3D CNWs/G architecture overcomes the drawbacks of presently available 3D graphene products and opens up a wide horizon for structural, electronic, thermal transport, intramolecular junction, heterogeneous catalysis, electrochemical energy storage, and etc. Graphical abstract: